GIS-Based Approach For Mapping Of Chemical-Based Pollutant Concentration Along The Galing River, Kuantan - Zainudin, Ahmad Zabidi (2023)
Water is the primary source of life for humans, microbes, and other living things. Water pollution research should be done in order to avoid and curbed the source from becoming a rare resource that is difficult to obtain. Sediment, oil, and chemical-based pollutants are among the water contaminants. Pollutants have had a significant influence on the environment, including the air, water, and humans. Among them, the water's color will darken from its initial hue. Furthermore, the pollution will have an impact on aquatic life in the water. As a result of the pollution, people will run out of seafood resources, or seafood will become limited. This has demonstrated that treating the water will have a substantial influence on multiple parties. This may be seen in Sungai Galing, which has been contaminated by many sorts of pollutants, causing the water's behaviour to vary in terms of colour, pH level, dryness, and other aspects. Finally, water must be handled and cared for so that the resource is not depleted and limited.